Developing a smart system for human resource management thru mobile application - Noraishah Shafiqah Binti Yacob (2023)
Volunteering is a fundamental component that gives value of our culture, society and environment. We always believe from a far broader angle and that is why individuals agree to work without pay. It is somehow appealing for us to work for a non-profit organization that benefits society. This aimed of this study is to encourage volunteerism. It is widely recognized that individuals have a powerful desire to work for themselves but never go any further because it can be a tedious job to seek a volunteer event that suitable with their passion. A prototype of volunteer mobile application will be designed to address this problem so that it can be used for volunteering and for creating own volunteering event. This mobile application has been intended to be user-friendly so that all age group can be taken into consideration. Consequently, the prototype shows that the design can functions well with the actual mobile application. The mobile application should be ergonomically friendly for the end users